An aesthetic-musical crossroad: Music of the future by Richard Wagner - Mesquita, Marcos [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2015)
The essay Music of the future by Richard Wagner was written in a critical moment in composer's life. He was attempting to take distance from concepts disseminated by him in former texts, and has clearly perceived the distance between his theoretical ideals of the 1840' s about the total work of art (Gesamtkunstwerk) and his compositional practice of the 1850's. The text bellow investigates the contradictions between Wagnerian reflection and practice during the mentioned period.
Keywords: Richard Wagner; Ludwig Feuerbach; Arthur Schopenhauer; music of the future; musical drama; aesthetics